2020
DOI: 10.1002/cphc.201900904
|View full text |Cite
|
Sign up to set email alerts
|

In Silico Evidence That Protein Unfolding is a Precursor of Protein Aggregation

Abstract: We present a computational study on the folding and aggregation of proteins in an aqueous environment, as a function of its concentration. We show how the increase of the concentration of individual protein species can induce a partial unfolding of the native conformation without the occurrence of aggregates. A further increment of the protein concentration results in the complete loss of the folded structures and induces the formation of protein aggregates. We discuss the effect of the protein interface on th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 22 publications
(40 citation statements)
references
References 83 publications
(195 reference statements)
4
36
0
Order By: Relevance
“…To tackle computationally the folding/aggregation problem in solutions involving tens of proteins we adopt a coarse-grain model for protein solvated by water, [23][24][25][26][27][28][29] based on a wa-ter model that reproduces-at least qualitatively-the thermodynamic properties of the sol-vent. [30][31][32] We perform Monte Carlo simulations to design artificial protein structures, with a well tested scheme, 33,34 recently extended to optimize the protein sequence to the water properties at a given temperature and pressure.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To tackle computationally the folding/aggregation problem in solutions involving tens of proteins we adopt a coarse-grain model for protein solvated by water, [23][24][25][26][27][28][29] based on a wa-ter model that reproduces-at least qualitatively-the thermodynamic properties of the sol-vent. [30][31][32] We perform Monte Carlo simulations to design artificial protein structures, with a well tested scheme, 33,34 recently extended to optimize the protein sequence to the water properties at a given temperature and pressure.…”
Section: Resultsmentioning
confidence: 99%
“…when solvated in heterogeneous solutions (multiple copies of different proteins) compared 4 to their aggregation concentration (determined in our previous study23 ) in homogeneous solutions (multiple copies of the same protein). Finally, we have verified these conclusions experimentally by the evaluation of the aggregation behaviour of two model proteins, the bovine serum albumin (BSA) and the consensus tetratricopeptide repeat (CTPR).…”
mentioning
confidence: 98%
“…The amino acids interact through the nearest neighbor potential given by the Miyazawa-Jerningan interaction matrix [49]. To account for the lower surface-volume ratio in 2D, we scale the matrix by a factor of 2, increasing the effective amino acids interactions [30].…”
Section: Protein and Interface Modelmentioning
confidence: 99%
“…For example, a recent study showed that the concentration increase of individual protein species can unfold their native state without inducing their aggregation [30]. Furthermore, each component in a protein mixture can keep its folded state at densities that are larger than those at which they would precipitate if they were in a single-specie solution [31].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation